ANGKA ASAL MASALAH PADA KASUS AUL DAN METODE PENYELESAIANNYA DALAM WARIS ISLAM; Analisis dan Aplikatif - Ritonga, Raja; Putra, Dedisyah (Fakultas Syariah (Syari'ah Faculty ), 2023)
The number of basic problem in inheritance case is the first factor in determining of the share value. In common, the total share of all the heirs at every case is equal to the number of basic problem. Because of the number of basic problem is the illustration of the property value which divided by the heirs. However, the number of share from all the heirs’ combination can be difference with the basic problem. Then, this research describes about the numbers of basic problem and the differences of share total and the basic problem at heirs’ case. The kind of this research is a library research with the qualitative and conceptual approach model. Afterwards, it analyzed with the content analysis. The result explained that the numbers of basic problem can be taken from the denominator number of heirs’ portion or KPK from it denominator number. The numbers of basic problem are only seven; they are 2, 3, 4, 6, 8, 12, and 24. Three of them are 6, 12 and 24. While the number 2, 3, 4 and 8 will not happened ‘aul in finishing heirs’ case. The problems of ‘aul is the heirs’ case when the total of share of the whole heirs is bigger than the number of basic problem. For its finishing, the combination share of all heirs become as the basic new problem to change the first basic problem. Then, to know the value of share, all of wealth is divided with the second problem, it is not with the first basic problem.